From research to innovation policy in Vietnam - Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Using the approach of “Policy culture” in public policy analysis in the fields of scientific research, technology development and innovation, the article analyses the dynamic and evolutionary transition of science, technology and innovation (STI) policy in Vietnam is divided into three policy generations - from linear innovation to interactive innovation and recently transformative innovations. Code: 21020501